1924
DOI: 10.1017/s0021859600003993
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of the development of the wheat grain

Abstract: The connection which has been shown to exist between the strength of wheat flour and the chemical individuality of the glutenine fraction of the wheat protein (Woodman, 1922) (1) led the writers to institute an enquiry into the manner in which the individual wheat proteins are developed and stored during the progress of the grain from the early stages after flowering to ripeness. The immediate object of the investigation was to secure information in regard to the stages at which the different proteins made the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1935
1935
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…This is consistent with results of previous workers (Benetrix et al, 1994;Gupta et al, 1996). Woodman and Engledow (1924) found that the appearance of gluten properties corresponded to the beginning of grain desiccation. Stone and Nicolas (1996a) reported a strong correlation (r= 0.91, P <0.01) between formation of large glutenins and grain desiccation.…”
Section: The Role Of the Desiccation Phasesupporting
confidence: 93%
“…This is consistent with results of previous workers (Benetrix et al, 1994;Gupta et al, 1996). Woodman and Engledow (1924) found that the appearance of gluten properties corresponded to the beginning of grain desiccation. Stone and Nicolas (1996a) reported a strong correlation (r= 0.91, P <0.01) between formation of large glutenins and grain desiccation.…”
Section: The Role Of the Desiccation Phasesupporting
confidence: 93%
“…This increase in molecular weight usually correlates with an increased dough-forming ability (Woodman and Engledow 1924) and dough strength (MacRitchie 1973;Gupta et al 1993;Gupta and MacRitchie 1994;Gupta et al 1995). It is therefore possible that heat stress, by reducing the duration of grain-filling, could reduce the average molecular weight (and contribution to dough strength) of wheat proteins, with a consequent reduction in dough strength.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot explain this phenomenon, although it appears that high temperature increased the extent to which albumin/globulin proteins may have been reconstituted into other classes of protein. There has been some speculation about this mechanism (Woodman and Engledow 1924;Flint et al 1975;Cressey et al 1987), but it has proved difficult to provide empirical evidence of its existence (Graham and Morton 1963;Graham et al 1963).…”
Section: Time (Days After Anthesis)mentioning
confidence: 99%